Edukasi Penerapan Budaya 5S (Senyum, Salam, Sapa, Sopan dan Santun) dalam Kehidupan Sosial Anak Panti Asuhan Yayasan Nischaya Indonesia di Kecamatan Medan Selayang Kota Medan - Rika Puspita Sari; Ira Revina; Muniroh Muniroh; Dwiki Kurniansyah; Ester H Sitindaon (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
The Orphanage is considered as a shelter for neglected children where this Orphanage can guarantee the lives of foster children. By providing attention, affection, guidance, and direction of behavior in accordance with good values ​​and norms as well as non-formal and formal education which is also given appropriately for children living in orphanages. Through the Nischaya Indonesia Foundation Orphanage, Kec. Medan Selayang, Medan City, accommodates Nias children, such as orphans and orphans, as well as underprivileged children. Through observation and interviews it can be seen how the service system of the Panti is. Then it was found that there were various different behaviors, especially individualism which often changed. The before after implementation method is in the form of outreach to the orphanage children of the Indonesian Niscaya Foundation by providing education about the 5S culture (Smile, Greeting, Greet, Polite and Polite). The result of implementing the 5S culture is being able to have good manners and an attitude of mutual respect for the surrounding environment.